(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
ABSTRACT This experience report mainly focuses on university extension operations through the Rondon Extension Center (NER/UDESC) and its consequences. It aims to present the author’s understanding of the concept of university extension in Brazil and their participation in extension activities related to NER/UDESC, in addition to demonstrating the relevance of the impact and student transformation provided by university extension.